On the dynamic response of a poroelastic medium subjected to a moving load based on nonlocal Biot theory. (June 2021) - Tong, L.H.; Ding, Haibin; Zeng, Luolan; Geng, D.X.; Xu, C.J.
Abstract: Based on classical Biot poroelastic theory and nonlocal elastic theory, an analytical model for investigating the dynamic responses of saturated porous materials subjected to a moving load is proposed. The displacement and stress fields in the frequency and wavenumber domains are obtained through Fourier transform. Then, the double inverse Fourier transform is applied to the obtained displacement and stress solutions to give the results in the time–space domain. The influences of the nonlocal parameter and load moving speed on the displacement field are discussed in detail. The influence of the nonlocal parameter on the displacement is enhanced with increasing load moving speed. Furthermore, the increase in the nonlocal parameter results in a decrease of the " resonance-like " frequency in a saturated material, reducing the critical load moving speed. The influence of the damping ratio is also investigated; as expected, a higher damping ratio always reduces the displacement. Finally, the influences of the nonlocal parameter on the pore pressure and permeability are presented.